2009
DOI: 10.21273/hortsci.44.7.1884
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Aminoethoxyvinylglycine on Pecan Fruit Retention

Abstract: Insufficient fruit retention limits profitability of certain pecan [Carya illinoinensis (Wangenh.) K. Koch] cultivars. The present study examined efficacy of aminoethoxyvinylglycine (formulated as ReTain®; Valent BioSciences, Libertyville, IL), a natural ethylene inhibitor, for increasing crop-load through increased fruit retention in pecan trees grown at three distinct locations within the U.S. pecan belt. Several years of field studies found that timely postpollination ReTa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 27 publications
2
12
1
Order By: Relevance
“…Observations indicate that relatively low potassium (K + ) concentration, based on leaf analysis, of what appear to be well-managed 'Desirable' orchards, often exhibit excessive Stage II fruit drop (i.e., many peduncles having lost 75% to 100% of their fruit) and lower than expected nut yields, thus leading the authors to postulate that insufficient K nutrition during early stages of fruit development is a contributing cause of Stage II drop. This postulate is further supported in that 1) there is rapid accumulation of K + in tree organs after bud break; 2) K is the dominate metal in pecan fruit, especially in shuck (involucre) tissue in which its concentration increases up to eightfold during fruit enlargement ; and 3) there is evidence for a physiological stressor, perhaps a mineral nutrient, contributing to drop in ''moderate to heavy'' crop load trees (Wood et al, 2009). The present study examines whether increasing tree K can reduce Stage II fruit drop and subsequently increase tree nutmeat yield and quality.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Observations indicate that relatively low potassium (K + ) concentration, based on leaf analysis, of what appear to be well-managed 'Desirable' orchards, often exhibit excessive Stage II fruit drop (i.e., many peduncles having lost 75% to 100% of their fruit) and lower than expected nut yields, thus leading the authors to postulate that insufficient K nutrition during early stages of fruit development is a contributing cause of Stage II drop. This postulate is further supported in that 1) there is rapid accumulation of K + in tree organs after bud break; 2) K is the dominate metal in pecan fruit, especially in shuck (involucre) tissue in which its concentration increases up to eightfold during fruit enlargement ; and 3) there is evidence for a physiological stressor, perhaps a mineral nutrient, contributing to drop in ''moderate to heavy'' crop load trees (Wood et al, 2009). The present study examines whether increasing tree K can reduce Stage II fruit drop and subsequently increase tree nutmeat yield and quality.…”
mentioning
confidence: 93%
“…Stage I drop (bloom drop) is associated with poor pistillate flower development in consequence of insufficient access to resource reserves (Finch and Crane, 1931;Gossard, 1933;Smith, 1982;Sparks, 1988;Sparks and Heath, 1972;Sparks and Madden, 1985;Yates and Sparks, 1994). Stage II drop (June drop) is the first postpollination drop (Sparks and Madden, 1985) and can be associated with absence of zygotes or structural problems with ovule tis-sues Sparks, 1994, 1995) and might also be associated with physiological stresses accentuated by ''moderate to heavy'' crop loads (Wood et al, 2009). Depending on genotype, this drop is complete within %3 to 5 weeks (usually by mid-June) after stigmas of pistillate flowers lose receptivity and fruit begin slow elongation growth before rapid fruit enlargement at the end of the canopy growth phase.…”
mentioning
confidence: 99%
“…Serr) cultivars (Anderson et al, 2006;Beede and Polito, 2003;Buchner et al, 2006) and certain other tree or vine fruit crops (Belding and Lokaj, 2002;Bregoli et al, 2002;Byers, 1997Byers, , 1998aByers, , 1998bClayton et al, 2000;Dal-Cin et al, 2008;Greene, 2002Greene, , 2005Greene, , 2006Greene and Schupp, 2004;Hayama et al, 2008;Hu et al, 2002;Rath et al, 2006;Salazar-Garciìa et al, 2006;Schupp and Greene, 2004;Shafer et al, 1997;Webster et al, 2006;Williams, 1980). The product may therefore exhibit potential as a horticultural tool for crop load management in pecan (Wood et al, 2009). ReTain's ability to block ethylene biosynthesis, and therefore potentially inhibit Stage II fruit drop in pecan, is consistent with ethylene playing a key role in the abortion of developing pecan fruit, as has been previously implicated (Kays et al, 1975;Wood, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…AVG, formulated as ReTain, possesses potential as a horticultural tool for preventing or reducing unwanted fruit drop in pecan by interfering with endogenous ethylene biosynthesis, presumably by competitively inhibiting 1-aminocyclopropanecarboxylate synthase (Wood et al, 2010;Yu et al, 1979), the rate-limiting enzyme in the apparent primary ethylene anabolic pathway. Wood et al (2009) observed earlier that AVG, or ReTain, conditionally exhibits efficacy for reducing 'Desirable' fruit drop, thus justifying further evaluation in a real-world large commercial orchard environment. The value of AVG, or ReTain, as a horticultural tool in pecan horticulture depends on how the effects of increased fruit retention interact with pecan's natural ''off-on'' alternate bearing cycle (i.e., alternating cycles of few or no fruit followed by heavy fruit crops), which is driven in part by previous season crop load (Smith et al, 1993;Sparks, 1974;Wood, 2003;Wood et al, 2003).…”
mentioning
confidence: 92%
See 1 more Smart Citation